Foresighting future climate change impacts on fisheries and aquaculture in vietnam - Nhuong Tran; Chin Yee Chan; Yee Mon Aung; Bailey, Conner; Akester, Michael J.; Quyen Le Cao; Tu Quang Trinh; Cuong Van Hoang; Sulser, Timothy B.; Wiebe, Keith D. (Frontiers Media, 2022)
The Vietnamese fisheries sector, including both marine fisheries and aquaculture, has made spectacular progress in recent years, becoming one of the top seafood producing and exporting countries in the world. Looking forward, development goals of this sector must address challenges associated with climate change, including changing distribution of commercially important marine species such as tuna and disruptions to land-based aquaculture production systems. This study investigates the prospective climate change impacts on Vietnam's fisheries sector, focusing on four key commodities including capture fisheries (tuna), freshwater aquaculture (pangasius catfish and tilapia), and brackish water aquaculture (shrimp). The extent of impact varies, but climate change represents a potentially significant threat to sustainable production in each production system. Producers, policy makers, and other stakeholders need to plan for and adapt to climate change to ensure the sustainable development of Vietnam's fisheries sector.